PENGARUH KEPEMIMPINAN TERHADAP PARTISIPASI MASYARAKAT DESA SEREANG KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - Asrul Alwi; Nurjannah Nonci; Erfina Erfina (JIA: Jurnal Ilmiah Administrasi, 2021)
This study aims to: 1. find out the influence of leadership style on community participation in Sereang Village, Maritengngae District, Sidenreng Rappang Regency. 2. To find out the factors that influence the leadership style in Sereang Village, Maritengngae District, Sidenreng Rappang Regency. The population in this study is 779, with a sample of 78 people. The sampling technique used is random sampling or random sampling. Data collection techniques used 1. Observations 2. library studies 3. cetets (questionnaire). The collected data is then analyzed with the help of SPSS 16 for Windows applications. The results showed that 1. the influence of leadership style on community participation in Sereang Village Maritengngae District, Sidenreng Rappang District was in the unfavorable category with a percentage of 31.7%. 2. What factors influence the leadership style in Sereang Village, Maritengngae District, Sidenreng Rappang Regency are: Strength based on coercion (17.7%), Strength of appreciation (26%), Strength of expertise (19.5%), Official strength (11 , 9%), Strength of reference (14.4%).